Establishing the principles in Halal logistics / Marco Tieman - Tieman, Marco (Faculty of Business and Management, 2013)
This research paper aims to establish the principles of halal logistics. This exploratory research paper is based on a large discussion group held in Malaysia to define the scope of halal logistics, its principles and foundation for Muslim and non-Muslim countries. Halal logistics covers warehousing, transportation and terminal operations. The establishment of these principles serves as a guide for the creation of a global halal logistics system; minimising hardship for the halal industry; define cross-contamination between halal and haram and how to avoid it; create an evolution of a complete halal value chain and supply chain; and benchmark with existing standards and best practices. For Muslim countries, halal logistics is based on avoiding direct contact with haram, addressing the risk of contamination, and perception of the Muslim consumer. For non-Muslim countries, halal logistics is only based on avoiding direct contact with haram and addressing the risk of contamination. Since this paper is an exploratory study, it provides some insights into the minimum and preferred level of halal logistics in Muslim and non-Muslim countries. However, quantitative research is needed to confirm this difference in consumer perception between Muslim and non-Muslim countries